Pengaruh Pendidikan Etika Bisnis dan Religiusitas terhadap Persepsi Etis Mahasiswa Akuntansi: (Studi Empiris pada Universitas Nusa Nipa Maumere) - Sisilia Anggreachi Teras; Andreas Rengga; Wilhelmina Mitan (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2024)
The research aimed to investigate how Business Ethics Education and Religiosity affect the ethical perception of Accounting Students at Nusa Nipa University, Maumere. The research follows an associative approach with a causal relationship form and utilizes a quantitative approach. The sampling technique used Probability sampling type Random sampling, with a sample size of 76 respondents. Data the Social Sciences (SPSS) version 23. The results of this research indicated that: (1) Business Ethics Education had a positive influence on the Ethical Perception of Accounting Students. (2) Religiosity had a positive influence on the Ethical Perception of Accounting Students. (3) Business Ethics Education and Religiosity had a Simultaneous influence on the Ethical Perception of Accounting Students at Nusa Nipa University, Maumere.